External adjustment in small open economies: Some recent experience - Johnny Åkerholm (Bank of Finland, 1988)
The paper deals with the adjustment problems that small open economies face in a financially integrated world. Particular attention is paid to the assignment of different policy instruments te the achievement different policy targets. It is concluded that the· possibilities to use monetary and fiscal policy instruments are highly dependent on the flexibility of wages and prices. It is, however, likely that monetary policy has to be increasingly geared towards the containment of inflation, while fiscal pol~cy has to secure external balance. The pessibilities to maintain employment is thus largely dependent on wage and price behaviour. The adjustment process of Australia, Denmark and Sweden is analyzed in order to shed some light on the role of the policy mix and to evaluate the importance of wage and price flexibility and the factors which influence the degree of flexibility.
URN:NBN:fi:bof-201807301737
Keywords: 330